Le discours et ses situations - Rey-Debove, Josette (Studia Romanica Posnaniensia, 2007)
This paper aims to situate the various areas of discourse analysis with respect to general typological or intersecting characteristics, and to èxtend our apprehension of «true meaning» as far as possible. It suggests that unacceptable phrases and paralinguistic elements can be included in semantics, and that non-spontaneous cited or transcribed discourse can be considered alongside spontaneous oral and written discourse. A distinction is made between the «producer» (who is «responsible») and the «emitter»; between the «addressee» (who is deliberately targeted) and the «receiver». The emitter is often citing a third party, while the addressee is often non-specific or accidental. Provision is made for conflictual relationships between speakers (claiming the right to speak in public) and messages with pseudo addressees, which give the function of expression priority over the function of communication. The phatic function merely maintains a relationship between speakers which is detrimental to meaning, just as violence may ensue when intercomprehension breaks down.